A more-than-human perspective on understanding the performance of the built environment. (3rd July 2020) - Loh, Susan; Foth, Marcus; Caldwell, Glenda Amayo; Garcia-Hansen, Veronica; Thomson, Mark
Abstract : The ready availability and widespread deployment of IoT devices and sensors enable a high granularity of quantitative data to be collected to give a real-time appraisal of a building's environmental performance. Rating and assessment frameworks are increasingly taking advantage of insights that can be derived from both new building technology and big data analytics. Yet, climate change action requires new perspectives that move towards a post-anthropocentric and more-than-human viewpoint. This paper makes a threefold contribution. In order to highlight a gap, we (1) critique select Green Building Rating Tools, (2) contrast current achievements and targets with what climate change action demands of the built environment's performance; and (3) we discuss several causes for the disconnect between actual and aspirational ends of the performance measurement spectrum and offer some possible responses and actions with a view to stimulate scholarly debate and engagement to leapfrog the performance of the built environment.